Analisis Nilai Personal Pada Cerita Anak Berjudul Chaditsu Baina As-Syajarah Wa Al-‘Ushfur Karya Ismail Abidin - Fero Cahya Nagara (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2025)
This study focuses on personal values in a children's story entitled Chadi>tsu Baina As-Syajarah wa Al-'Ushfur by Dr. Isma'il 'Abidin. This research is a literature study research using qualitative descriptive methods using personal value development analysis. In this development analysis will describe the value of development; (a) emotional, (b) intellectual, (c) imaginary, (d) social sense, and (e) ethical and religious sense contained in the story. The results showed that in the story there is complete personal value. Child readers are not only entertained by the presentation of short stories, but will also get education according to their age stage. This story teaches about the importance of preserving nature, fostering empathy and social traits. Reading this novel is recommended for children aged 6-12 years as learning with the guidance of parents or teachers.